17β-Estradiol infusions into the dorsal striatum rapidly increase dorsal striatal dopamine release in vivo. (25th August 2016) - Shams, Waqqas M.; Sanio, Christian; Quinlan, Matthew G.; Brake, Wayne G.
Highlights: Striatal dopamine levels were measured in vivo in response to amphetamine. Estradiol in the striatum enhanced dopamine release. Estradiol in the prefrontal cortex did not affect striatal dopamine release. Estradiol in the substantia nigra either increased or decreased striatal dopamine. Abstract: Systemic injections of 17β-estradiol (E2) in ovariectomized (OVX) female rats rapidly enhance dorsal striatal dopamine (DA) release in response to amphetamine (AMPH). Additionally, a single injection of E2 rapidly (within 30 min) enhances amphetamine-induced DA release. In situ studies show that this rapid effect of E2 occurs specifically within the dorsal striatum (DS). The present study investigated the in vivo effects of E2 infused into the DS, medial prefrontal cortex (mPFC) or the substantia nigra (SN) on dorsal striatal DA release. Rats were OVX and implanted with a silastic tube containing 5% E2 in cholesterol, previously shown to mimic low physiological serum concentrations of 18–32 pg/ml. Single-probe microdialysis was used to measure extracellular DA levels in the DS. In addition, DA release was measured subsequent to systemic injections of the indirect DA agonist, AMPH (0.5 mg/kg SC), administered simultaneously with E2 (0.544 μg/100 μl) or its vehicle, cyclodextrin (VEH) (0.520 μg/100 μl). Local infusions of E2 into the DS resulted in a greater amphetamine-induced dorsal striatal DA release in comparison to vehicle. Local infusions of E2 into the mPFC or the SN did not result in an enhancement of amphetamine-induced DA levels in the DS. These studies suggest that increases in dorsal striatal DA release in response to systemic E2 are a consequence of E2 actions within the DS itself.